Environmental studies of the Khorramrood River in Iran, based on transformed high-resolution remotely sensed spectroscopic data - Paria Darvishi; Danya Karimi (Egyptian Journal of Remote Sensing and Space Sciences, 2024)
An investigation was conducted on the Khorramrood River in Iran to evaluate pollution levels resulting from human activities. Water samples were collected from eleven stations and analyzed for four parameters: pH, temperature, dissolved oxygen (DO), and nitrate (NO3). Additionally, a biodiversity assessment of macroinvertebrates was conducted to evaluate water quality. Eleven invertebrate families from seven classes were identified, with Chironomidae and Baetidae as the predominant groups, suggesting a significant deterioration in water quality. As the first objective, water quality assessment using macroinvertebrates was done using two diversity indices (Shannon-Wiener and Simpson) and four biotic indices (ASPT, FBI, EPT, and BMWP). The results consistently indicated poor water quality in the river. These findings are consistent with the conclusions drawn from the analysis of physicochemical parameters, which is the second objective, and both confirm inadequate water quality. As a part of the last objective, to map the physicochemical parameters, three scenarios were used. They involved utilizing a transformed high-resolution PRISMA image, a traditional method with Landsat 9 images, and a fusion of Landsat 9 and PRISMA images. The first scenario produced the most accurate results (RMSE = 0.624, 0.942, 0.167, and 0.98 for DO, NO3, pH, and temperature. respectively). Mapping biodiversity indices, another part of the last objective, using the transformed pan-sharpened PRISMA image proved highly reliable. A strong correlation was observed between most indices and the DO (CR = 0.972, −0.496, −0.973, and −0.978 for Simpson, EPT, BMWP, and ASPT, respectively), indicating the significant influence of DO on the river's biological state.